Therapeutic Communication Relationship With The Level of Anxiety of Primigravida Mother in Facing Childbirth At TK IV Hospital Cijantung Kesdam Jaya in 2023 - Susilowati, Lilik; Putri, Kinkin Y S; Reflisiani, Dian (Informasi, 2024)
One factor that affects the safety of labor is anxiety during the labor process. Anxiety and fear can cause severe pain and can also result in decreased uterine contractions, resulting in longer labor. The purpose of this study is to determine the relationship between therapeutic communication and the anxiety level of primigravida mothers in facing labor. This research type is descriptive-analytic. This study population is all primigravida laboring mothers in TK IV Cijantung Kesdam Jaya Hospital in 2023, as many as 30 people. Samples of this study were all primigravida pregnant women before childbirth at TK IV Cijantung Kesdam Jaya Hospital in January–February 2023, with as many as 30 respondents. The technique of sampling in this study was purposive sampling. Analyze the data with Chi Square. The statistical test results obtained P value = 0.000 means P value < Î± (0.05). The results indicate that there is a relationship between therapeutic communication and the level of anxiety of primigravida mothers in the face of childbirth. It is expected that TK IV Cijantung Kesdam Jaya Hospital will improve health services for mothers in labor by managing the application of therapeutic communication by midwives in providing care to mothers in labor.